The Influence of Viral Marketing and Halal Awareness on Purchasing Decisions at The Mie Gacoan Branch Dr. Mansyur Medan - Nabila; Hasman, Haryaji Catur Putera; Siregar, Dahrul (Journal Of Management Analytical and Solution (JoMAS), 2024)
This study was conducted to determine the effect of viral marketing and halal awareness on purchasing decisions at the Dr. Mansyur Medan branch of Mie Gacoan. In this study using quantitative research, quantitative research can be interpreted as a research method based on the philosophy of positivism, used to research on certain populations or samples, characteristics and relationships between variables whose data collection techniques use questionnaires. Data collection in this study was carried out slot zeus through distributing questionnaires using a Likert scale. The sample in this study were Gacoan Noodle Consumers totaling 97 respondents. The technique used to analyze data using Multiple Linear Regression Analysis with the help of SPSS Software. The results showed that the partial test of viral marketing variables had a positive and significant effect on purchasing decisions at Mie Gacoan, Dr. Mansyur Medan branch. The halal awareness variable has a positive and significant effect on purchasing decisions at Mie Gacoan, Dr. Mansyur Medan branch, and in the simultaneous test the viral marketing variable and the halal awareness variable together have a positive and significant effect on purchasing decisions at Mie Gacoan, Dr. Mansyur Medan branch. In the Coefficient of Determination test, the Adjusted R Square value is 0.562 (56.2%) and the rest is influenced by other factors.